Spin-phonon coupling and high-temperature phase transition in multiferroic material YMnO3. Issue 44 (21st October 2015) - Gupta, Mayanak Kumar; Mittal, Ranjan; Zbiri, Mohamed; Sharma, Neetika; Rols, Stephane; Schober, Helmut; Chaplot, Samrath Lal
Abstract : The comparison of the experimental and first-principles calculated phonon spectra highlights unambiguously a spin-phonon coupling in YMnO3 . Abstract : We have carried out temperature-dependent inelastic neutron scattering measurements of YMnO3 over the temperature range of 50–1303 K, covering both the antiferromagnetic to paramagnetic transition (70 K), as well as the ferroelectric to paraelectric transition (1258 K). Measurements are accompanied by first principles calculations of phonon spectra for the sake of interpretation and analysis of the measured phonon spectra in the room temperature ferroelectric ( P 63 cm ) and high temperature paraelectric ( P 63 / mmc ) hexagonal phases of YMnO3 . The comparison of the experimental and first-principles calculated phonon spectra highlights unambiguously a spin-phonon coupling character in YMnO3 . This is further supported by the pronounced differences in the magnetic and non-magnetic phonon calculations. The calculated atomistic partial phonon contributions of the Y and Mn atoms are not affected by the inclusion of magnetic interactions, whereas the dynamical contribution of the O atoms is found to change. This highlights the role of the super-exchange interactions between the magnetic Mn cations, mediated by O bridges. Phonon dispersion relations have also been calculated, in the entire Brillouin zone, for both the hexagonal phases. In the high-temperature phase, unstable phonon mode at the K point is highlighted. The displacement pattern at the K -point indicates that the freezing of this mode along with the stable mode at the Γ -point may lead to a stabilization of the low-temperature ( P 63 cm ) phase, inducing ferroelectricity. Furthermore, we have also estimated the mode Grüneisen parameter and volume thermal expansion behavior. The latter is found to agree with the available experimental data.